Formation of perioesophageal plexus gulae and anterior and posterior vagal trunks in South Indian Population : A morphological study - Amudha Govindarajan (Wolters Kluwer Medknow Publications, 2012)
Background and Aim of the study: Vagus the wanderer is the tenth cranial nerve with long extra cranial course. Below the bifurcation of trachea, the right and left vagi form plexus around the oesophagus before they enter the abdomen as anterior and posterior vagal trunks. There are variations in the contribution by the right and left vagi for the formation of oesophageal plexus and according to Chamberlin and Winship there are three different patterns in the formation of peri oesophageal plexus. The present study was aimed to study the formation of perioesophageal plexus, incidence of different patterns of peri oesophageal plexus in south Indian population and the number of vagal trunks formed from the oesophageal plexus in the lower end of the oesophagus. Materials and Methods: The formation of perioesophageal plexus Gulae was studied in forty four autopsy specimens of oesophagus and stomach and six foetal specimens at Institute of Anatomy, Madras Medical College, Chennai. Results: The formation of perioesophageal plexus and the number of fibres from the right and left vagus nerves which contribute to the plexus formation were studied. There were significant differences in the formation of plexus Gulae. There were variations in the pattern of perioesophageal plexus and the number of vagal trunks arising from the plexus. The results of the present study in South Indian population were compared with the results in the Western population. Conclusions: Awareness regarding the presence of plexus Gulae and number of vagal trunks related to lower end of oesophagus has considerable importance in the surgical repair of hiatus hernia and while treating atrial fibrillation.